Genotypic and phenotypic characterization of biofilm production by Staphylococcus aureus strains isolated from bovine intramammary infections in Colombian dairy farms. Issue 10 (October 2019) - Torres, G.; Vargas, K.; Sánchez-Jiménez, M.; Reyes-Velez, J.; Olivera-Angel, M.
Abstract: The ability of Staphylococcus aureus to form biofilms is an important virulence factor because this has been associated with persistent bovine intramammary infections. Different mechanisms of biofilm formation have been described in S. aureus ; however, the process has been found to be mainly driven by the ica and bap genes. The presence of the ica and bap genes, as well as the biofilm formation in vitro were evaluated in 229 S. aureus strains isolated from bovine milk collected from different regions of Department of Antioquia, Colombia. Three different genotypes grouped into three separate clusters were identified from in vitro assays. Genotype 1 ( ica positive and bap negative) was the most prevalent (78.17%), followed by genotype 2 ( ica and bap positive) (12.66%) and genotype 0 ( ica and bap negative) (9.17%). Biofilm formation was observed in 81.26% of the strains from which 100% of genotype 2 isolates showed biofilm formation. The biofilms formed by genotype 2 isolates were also found to have the highest optical density (>2.4). These results showed that most of the S. aureus strains were capable of biofilm formation, suggesting the virulence potential particularly in bap -positive strains.